Therapeutic efficacy of albendazole against soil-transmitted helminthiasis in children measured by five diagnostic methods. - Johnny Vlaminck; Piet Cools; Marco Albonico; Shaali Ame; Mio Ayana; Giuseppe Cringoli; Daniel Dana; Jennifer Keiser; Maria P Maurelli; Leonardo F Matoso; Antonio Montresor; Zeleke Mekonnen; et al. (Public Library of Science (PLoS), 2019)
Background Preventive chemotherapy (PC) with benzimidazole drugs is the backbone of soil-transmitted helminth (STH) control programs. Over the past decade, drug coverage has increased and with it, the possibility of developing anthelmintic resistance. It is therefore of utmost importance to monitor drug efficacy. Currently, a variety of novel diagnostic methods are available, but it remains unclear whether they can be used to monitor drug efficacy. In this study, we compared the efficacy of albendazole (ALB) measured by different diagnostic methods in a head-to-head comparison to the recommended single Kato-Katz. Methods An ALB efficacy trial was performed in 3 different STH-endemic countries (Ethiopia, Lao PDR and Tanzania), each with a different PC-history. During these trials, stool samples were evaluated with Kato-Katz (single and duplicate), Mini-FLOTAC, FECPAKG2, and qPCR. The reduction rate in mean eggs per gram of stool (ERR) and mean genome equivalents / ml of DNA extract (GERR) were calculated to estimate drug efficacy. Principal findings and conclusions The results of the efficacy trials showed that none of the evaluated diagnostic methods could provide reduction rates that were equivalent to a single Kato-Katz for all STH. However, despite differences in clinical sensitivity and egg counts, they agreed in classifying efficacy according to World Health Organization (WHO) guidelines. This demonstrates that diagnostic methods for assessing drug efficacy should be validated with their intended-use in mind and that other factors like user-friendliness and costs will likely be important factors in driving the choice of diagnostics. In addition, ALB efficacy against STH infections was lower in sites with a longer history of PC. Yet, further research is needed to identify factors that contribute to this finding and to verify whether reduced efficacy can be associated with mutations in the β-tubulin gene that have previously been linked to anthelmintic resistance. Trial registration ClinicalTrials.gov NCT03465488.